Computer based instrumentation system for temperature measurement using RTD in matlab application - Faiz, Mohd Zabri (2008)
This project present the computer based instrumentation system designed for temperature measurement using Resistance Temperature Detector, RTD. This system operated by using Matlab application. This project were consists of 3 parts that are for instrument part, the hardware and the software. For instrument part, the Resistance Temperature Detector, RTD is called temperature sensitive resistor. It is positive temperature coefficient device which mean that the resistance increase with temperature. The Digital Thermometer 7563 was used for read the input value of temperature and also used as temperature reference. The function of Yokogawa Temperature Transmitter PT 100 is to change the value of temperature to current and transmitted to ammeter. The hardware used to interface the temperature instrumentation with the software (Matlab). The Advantech PCI-1710HG was used as the hardware to interface from 2793 Decade Resistance Box to the Matlab application for analysis the data and find the result. The system will be operated by using GUI Matlab. Graphical User Interface, GUI is the type of user interface which allows people to interact with electronic devices like computers. This system is compatible software and can work with Advantech PCI-1710HG. The user can use this system in two ways that in automatic function or in manual function. This system was developed to find actual UUT output, output error, average, standard deviation and uncertainty. It also can plot graph and save the picture.